2015
DOI: 10.1016/j.ymgmr.2015.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the MPS I-H knock-in mouse reveals increased femoral biomechanical integrity with compromised material strength and altered bone geometry

Abstract: Mucopolysaccharidosis type I (MPS I), is an autosomal recessive lysosomal storage disorder caused by a deficiency in the α-L-iduronidase enzyme, resulting in decreased enzymatic activity and accumulation of glycosaminoglycans. The disorder phenotypically manifests with increased urine glycosaminoglycan excretion, facial dysmorphology, neuropathology, cardiac manifestations, and bone deformities. While the development of new treatment strategies have shown promise in attenuating many symptoms associated with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…The abnormal femoral length in the early stage may be due to abnormalities in the growth plate caused by GAG accumulation in MPS I mice. 27 The osteoclast activity of the femur in this MPS I model was 4-fold higher than in wild-type femora. 28 Our study showed that there was no significant difference in femur length between 5-month-old MPS I mice and wild-type mice, suggesting that the abnormal femur length of this MPS I mouse model might return to normal at 5 months of age.…”
Section: Discussionmentioning
confidence: 67%
“…The abnormal femoral length in the early stage may be due to abnormalities in the growth plate caused by GAG accumulation in MPS I mice. 27 The osteoclast activity of the femur in this MPS I model was 4-fold higher than in wild-type femora. 28 Our study showed that there was no significant difference in femur length between 5-month-old MPS I mice and wild-type mice, suggesting that the abnormal femur length of this MPS I mouse model might return to normal at 5 months of age.…”
Section: Discussionmentioning
confidence: 67%
“…We sought to determine whether PC molecules accumulate in the lysosomes of LSD osteoblasts. Saos2 osteoblasts in which the alpha‐L‐iduronidase gene was deleted using CRISPR‐Cas9 technology (CRISPR‐IDUA) represent a disease model of mucopolysaccharidosis type I (MPS I), a lysosomal storage disorder with severe skeletal manifestations (Oestreich et al , ). Similar to cells treated with BafA1, CRISPR‐IDUA showed swollen lysosomes, suggesting an accumulation of undigested substrates in the lysosomal lumen (Fig I).…”
Section: Resultsmentioning
confidence: 99%
“…Canine animal models for MPS I tend to show milder manifestations compared to humans afflicted by the disease [170][171][172]. The introduction of exact mutations in mouse models provides insights into the genetics of the disease [173,174]. However, the small size and short lifespan of mice need to be considered when evaluating therapeutic efficiency.…”
Section: Animal Modelsmentioning
confidence: 99%